Assessment of bioaerosols in indoor air of glasshouses located in a botanical garden. (December 2019) - Kozdrój, J.; Frączek, K.; Ropek, D.
Abstract: Plants, like humans and pets, can be regarded as significant sources of airborne bacteria and fungi in different indoor environments. Especially abundant collection of distinct vegetation can be found in glasshouses of botanical gardens. However, bioaerosol concentrations, particle size distribution and species composition have not been studied in these facilities. Hence, the indoor air of glasshouses in a botanical garden was sampled with regard to bioaerosol quantitative and qualitative characteristics in comparison to those of the garden outdoor and adjacent street air. Both in winter and summer sampling times, higher concentrations of airborne bacteria and fungi were ascertained in the glasshouses compared to those detected at the outdoor sites. The respirable fraction of microorganisms prevailed, showing distinct contribution of fine bioaerosol particles in size below 4.7 μm (≤2.1 μm for bacteria in winter), within the indoor air. Distinct plant or soil derived bacteria and fungi, with the presence of potentially hazardous and allergenic agents, were identified in this environment. The results indicate that different plants, assembled in the closed area as the garden glasshouses, significantly affect the indoor air quality. The garden workers and visitors should be aware of higher exposure to bioaerosols in these facilities than in the outdoor air. Highlights: Collected plants and soil are major sources of bioaerosol particles in glasshouses. Increased concentrations of PM2.5 and PM1 favour the persistence of bioaerosols. Bioaerosols are predominated by respirable and fine particles in size below 4.7 μm. Gram-positive bacteria prevail in glasshouses and moulds in the garden outdoor. Pathogenic and opportunistic microorganisms can be found in the glasshouse air.